2021
DOI: 10.1155/2021/7031492
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression Effects of miR-424 and BMP2 on the Osteogenesis of Wharton’s Jelly-Derived Stem Cells

Abstract: Recently, the translational application of noncoding RNAs is accelerated dramatically. In this regard, discovering therapeutic roles of microRNAs by developing synthetic RNA and vector-based RNA is attracting attention. Here, we studied the effect of BMP2 and miR-424 on the osteogenesis of Wharton’s jelly-derived stem cells (WJSCs). For this purpose, human BMP2 and miR-424 DNA codes were cloned in the third generation of lentiviral vectors and then used for HEK-293T cell transfection. Lentiviral plasmids conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
(70 reference statements)
1
3
0
Order By: Relevance
“…In recent years, many studies [46][47][48] This study confirms that BMP2 has a significant ability to promote the proliferation and osteogenic differentiation of hPDLCs.…”
Section: The Mrna Expression Level Of Osteogenesisrelated Genessupporting
confidence: 68%
See 1 more Smart Citation
“…In recent years, many studies [46][47][48] This study confirms that BMP2 has a significant ability to promote the proliferation and osteogenic differentiation of hPDLCs.…”
Section: The Mrna Expression Level Of Osteogenesisrelated Genessupporting
confidence: 68%
“…In recent years, many studies 46–48 have shown that BMP2 plays an important role in tissue engineering and can significantly promote the osteogenic differentiation of stem cells. On the basis of previous studies, this study selected hPDLCs to explore the role of BMP2 in promoting osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…miR-216a was found capable of reversing the inhibiting effects of dexamethasone on the osteogenic process, while its expression levels were shown to positively correlate with osteoblastic differentiation and bone formation in adipose tissue-derived mesenchymal stem cells (ATMSCs) and UCMSCs [35]. Furthermore, it was demonstrated that an ex vivo engineered vector combining miR-424 and the bone morphogenetic protein-2 (BMP2) encoding gene has the capacity to promote osteogenesis in WJMSCs, with miR-424 potentially leading to the overexpression of OCN and BMP2 protein levels, the latter of which is considered an important regulator of the osteogenic/osteoblastic differentiation, and ultimately bone development [26].…”
Section: Osteogenic/osteoblastic Differentiationmentioning
confidence: 99%
“…Furthermore, RUNX2 can mediate the BMP-2-induced expression of OSX [ 113 ]. BMP2 is regulated by the downstream target genes WISP1 [ 114 ] and miR424 [ 115 ] of the Wnt signaling pathway, which enhances its induction of OSX. OSX is another important regulator of osteogenic differentiation.…”
Section: Combined Factors Mediate Osteogenic Differentiation Of Wj-mscsmentioning
confidence: 99%